THE INFLUENCE OF CAPITAL STRUCTURE (DER) AND PROFITABILITY (ROE) ON COMPANY VALUE IN VARIOUS INDUSTRIAL SECTORS LISTED ON THE INDONESIAN STOCK EXCHANGE (IDX) FOR THE 2014-2018 PERIOD - Nadia Yuliana; Hanun Natasha Salimah; Anah Tiyana (Cirebon International Conference on Education and Economics Proceeding, 2024)
The purpose of this study is to investigate how probability and capital structure affect company value. The different industrial sector corporations that list on the Indonesia Stock Exchange between 2014 and 2018 served as the study's unit of analysis. The test was decided based on the purposive examining strategy so that 9 companies were gotten inside a period of 5 a long time. Associative research, which seeks to establish a connection between two or more random variables, was the methodology employed. Yahoo Finance and financial reports are the sources of the data utilized; www.idx.co.id is the data source. This study's data analysis method was multiple regression linear, which has been used to examine traditional assumptions such as autocorrelation, heteroscedasticity, multicollinearity, and normality. handling data using IBM SPSS Version 26. The simultaneous F test and the partial T test were utilized in hypothesis testing. The findings indicated that although profitability has a negative and considerable impact on company value, the capital structure variable had a largely negligible and no influence. Additionally, the impact of profitability and capital structure on company value is substantial and powerful.